Question
upstudy study bank question image url

1. Given the sequence \( 6 ; 13 ; 20 ; \ldots \) a) Determine a formula for the nth term of the sequence. b) Calculate the 21 st term of this sequence. c) Determine which term of this sequence is 97 . 2. Consider this number pattern: \( 8 ; 5 ; 2 ; \ldots \) a) Calculate the \( 15^{\text {th }} \) term. b) Determine which term of this sequence is -289 . a) Given the arithmetic sequence \( 1-\mathrm{p} ; 2 \mathrm{p}-3 ; \mathrm{p}+5 ; \ldots \) b) Determine the values of the first three terms of the sequence.

Ask by Vaughn Rojas. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. a) The nth term is \( 7n - 1 \). b) The 21st term is 146. c) 97 is the 14th term. 2. a) The 15th term is –34. b) –289 is the 100th term. 3. For \( p = 3 \), the first three terms are –2, 3, and 8.

Solution

We’ll solve each part step by step. ───────────────────────────── 1. For the sequence 6; 13; 20; … a) Find a formula for the nth term. • The difference between consecutive terms is:   13 – 6 = 7  and  20 – 13 = 7. • Because the common difference d = 7 and the first term a₁ = 6, the nth term of an arithmetic sequence is given by:   aₙ = a₁ + (n – 1) × d • Plug in the values:   aₙ = 6 + (n – 1) × 7 = 6 + 7n – 7 = 7n – 1 b) Calculate the 21st term. • Using aₙ = 7n – 1 with n = 21:   a₂₁ = 7 × 21 – 1 = 147 – 1 = 146 c) Determine which term of this sequence is 97. • Set aₙ = 97:   7n – 1 = 97   7n = 98   n = 14 • Thus, 97 is the 14th term. ───────────────────────────── 2. Consider the number pattern: 8; 5; 2; … a) Calculate the 15th term. • The common difference is:   5 – 8 = –3  and  2 – 5 = –3. • The nth term is:   aₙ = a₁ + (n – 1) × d = 8 + (n – 1)(–3)   Simplify: aₙ = 8 – 3(n – 1) = 8 – 3n + 3 = 11 – 3n • For n = 15:   a₁₅ = 11 – 3×15 = 11 – 45 = –34 b) Determine which term of this sequence is –289. • Set aₙ = –289:   11 – 3n = –289   Subtract 11 from both sides:   –3n = –300   Divide by –3:   n = 100 • So, –289 is the 100th term. ───────────────────────────── 3. For the arithmetic sequence: 1 – p; 2p – 3; p + 5; … a) The sequence is arithmetic if the differences between consecutive terms are equal. That is,   [(2p – 3) – (1 – p)] must equal [(p + 5) – (2p – 3)]. • Compute the first difference:   (2p – 3) – (1 – p) = 2p – 3 – 1 + p = 3p – 4 • Compute the second difference:   (p + 5) – (2p – 3) = p + 5 – 2p + 3 = –p + 8 (which is the same as 8 – p) • Set them equal:   3p – 4 = 8 – p   Add p to both sides: 4p – 4 = 8   Add 4: 4p = 12   Divide by 4: p = 3 b) Determine the values of the first three terms of the sequence. • Substitute p = 3 into each term:   First term: 1 – p = 1 – 3 = –2   Second term: 2p – 3 = 2×3 – 3 = 6 – 3 = 3   Third term: p + 5 = 3 + 5 = 8 ───────────────────────────── Summary of Answers: 1. a) aₙ = 7n – 1  b) a₂₁ = 146  c) 97 is the 14th term 2. a) The 15th term is –34  b) –289 is the 100th term 3. For p = 3, the first three terms are –2, 3, and 8.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the first sequence \(6; 13; 20; \ldots\), we notice that it is an arithmetic sequence where the first term \(a_1 = 6\) and the common difference \(d = 7\) (since \(13 - 6 = 7\)). The formula for the nth term \(a_n\) of an arithmetic sequence can be expressed as: \[ a_n = a_1 + (n-1) \cdot d = 6 + (n-1) \cdot 7 = 7n - 1 \] To calculate the 21st term, substitute \(n = 21\): \[ a_{21} = 7 \cdot 21 - 1 = 147 - 1 = 146 \] To find which term equals 97, set the nth formula equal to 97 and solve for \(n\): \[ 7n - 1 = 97 \implies 7n = 98 \implies n = 14 \] For the second sequence \(8; 5; 2; \ldots\), this is also an arithmetic sequence with the first term \(b_1 = 8\) and common difference \(d = -3\) (since \(5 - 8 = -3\)). The formula for the nth term \(b_n\) is: \[ b_n = 8 + (n-1)(-3) = 8 - 3(n-1) = -3n + 11 \] Calculating the 15th term: \[ b_{15} = -3 \cdot 15 + 11 = -45 + 11 = -34 \] To find which term equals -289, set the nth formula equal to -289: \[ -3n + 11 = -289 \implies -3n = -300 \implies n = 100 \] For the arithmetic sequence defined with parameters \(1 - p\), \(2p - 3\), and \(p + 5\), we can identify the first three terms by simply substituting different \(p\) values. The first term is \(1-p\), the second term is \(2p - 3\), and the third term is \(p + 5\). To ensure that it is indeed an arithmetic sequence, we check if the common difference between consecutive terms holds true. The common difference \(d\) can be determined as: \[ d = (2p - 3) - (1 - p) = 3p - 4 \] \[ d = (p + 5) - (2p - 3) = 8 - p \] For these to be equal, we can solve \(3p - 4 = 8 - p\), leading to the determination of its characteristics depending on the relevant \(p\). If you want to explore more about arithmetic sequences, there are various resources available, ranging from textbooks to online platforms, all rich with examples and practice problems that make learning delightful! Also, be sure to check out math blogs and videos that creatively explain these concepts with real-world applications!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy